Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/mlr.0000000000001257
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Biomarkers for Patients With Diabetes After the Affordable Care Act

Abstract: Background: Racial and ethnic minorities are disproportionately affected by diabetes and at greater risk of experiencing poor diabetes-related outcomes compared with non-Hispanic whites. The Affordable Care Act (ACA) was implemented to increase health insurance coverage and reduce health disparities. Objective: Assess changes in diabetes-associated biomarkers [hemoglobin A1c (HbA1c) and low-density lipoprotein] 24 months pre-ACA to 24 months post-ACA Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…When these barriers to access are diminished, evidence suggests Hispanic patients may experience greater improvement in health outcomes relative to non-Hispanic whites ( Marino et al, 2020 ). The fact that racial and ethnic health disparities appear to be attenuated in CHCs compared to other healthcare settings ( Appel et al, 2006 ; Heintzman, Bailey, DeVoe, et al, 2017 ; Heintzman, Bailey, Muench, et al, 2017 ; Heintzman et al, 2018 ) underscores the importance of understanding the strategies CHCs have developed to deliver equitable care.…”
Section: Discussionmentioning
confidence: 99%
“…When these barriers to access are diminished, evidence suggests Hispanic patients may experience greater improvement in health outcomes relative to non-Hispanic whites ( Marino et al, 2020 ). The fact that racial and ethnic health disparities appear to be attenuated in CHCs compared to other healthcare settings ( Appel et al, 2006 ; Heintzman, Bailey, DeVoe, et al, 2017 ; Heintzman, Bailey, Muench, et al, 2017 ; Heintzman et al, 2018 ) underscores the importance of understanding the strategies CHCs have developed to deliver equitable care.…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the quality of care CHCs provide regardless of expansion status. Notably, previous studies have shown that gaining insurance in states that expanded Medicaid was associated with increase diabetes control, 29 especially among patients of Hispanic ethnicity receiving care in CHCs. Future studies are needed to assess whether the findings observed here differ by population subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Though the Affordable Care Act provisions increased insurance coverage, the findings continue to be relevant due to the persistence of racial and socioeconomic disparities. 23 , 24 Further, self-selection bias may contribute to a limited set of experiences or perspectives since online participation is voluntary. Individuals may be uncomfortable sharing private information, even if anonymous.…”
Section: Discussionmentioning
confidence: 99%